(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Meeting the projected growth in global electricity demand requires innovative and sustainable solutions aligned with net-zero ambitions. Co-located offshore renewable energy (ORE) systems, integrating wave energy converters (WECs) and floating offshore wind turbines (FOW) offer a promising alternative to address space constraints, improve reliability, and reduce environmental impact. This study presents a Life Cycle Assessment (LCA) of a co-located ORE system in Portugal, featuring a 30 MW wave energy array and a 300 MW floating offshore wind farm. Results from a cradle-to-grave evaluation indicate a carbon footprint of 17.7 gCO₂eq/kWh, a carbon payback period (CPBT) of 1.4 years and an energy payback period (EPBT) of 2.0 years. The carbon intensity falls between that of standalone FOW, typically less carbon-intensive, and wave energy, which has higher impacts due to their lower technological maturity and added complexity. By sharing infrastructure and streamlining operation and maintenance (O&M), the co-located system offsets some of the environmental burdens while enhancing the potential of energy production. The findings demonstrate a balanced trade-off between environmental impacts and energy benefits, also underscoring the potential of co-located ORE systems to support the development and commercial readiness of wave energy technologies, fostering innovation and cost reductions.